Technical progress, innovation and product differentiation in a Ricardian trade model with a continuum of goods - Harald Trabold (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
The Ricardian model is often considered of limited use and scope for the explanation of trade flows, as it cannot account for various important aspects of real world trade such as innovation goods or intra-industry trade. This is basically due to the fact that the Ricardian model is usually presented in the two-good, two-country form. However, using a Ricardian model with a continuum of goods does not only allow an analysis of the effects of technical progress or the production of new, innovative goods. It is also possible to explain intra-industry trade solely within the general setting of a Ricardian model.
Keywords: 330; Außenwirtschaftstheorie; Technologietransfer; Innovation; Außenhandel mit Industriegütern; Theorie